The Effectiveness of Using Misopostol and Oxytocin in Handling Post Partum Hemorrhage at the Rangga Medika Cikampek Clinic, Karawang Regency in 2022 - Tita Juwita; Achmad Fauzi (STIKep PPNI Jawa Barat, 2023)
Aims : This study aims to determine the effectiveness of the use of misoprostol and oxytocin in the treatment of postpartum hemorrhage at Rangga Medika Clinic, Karawang Regency in 2022. Methods : is an analytical method with a cross sectional approach. The research was conducted at Rangga Medika Clinic, Karawang Regency. Research data using observation sheets. The number of respondents as many as 30 people. Data analysis used dependent t-test. Results : The results showed that the results of the dependent t test (paired t test) showed that there was a difference in the use of misoprostol and oxytocin in the treatment of postpartum hemorrhage with p<0.05. Conclusions : The young age of the reproductive organs and inadequate physiological functions affect pregnancy acceptance and the postpartum period. The majority of respondents were of a healthy reproductive age between 20 and 35 years, with high-risk pregnancies occurring after that age.